Migrant Workers as Cultural Intermediaries - Madrah, Muna Yastuti; Suharko, Suharko (Universitas Negeri Semarang, 2019)
This article aims at proposing an analysis formula on how the mechanism of cultural intermediaries done by Indonesian migrant worker student. The subject of this study were Indonesia migrant worker students in Korea undertaking higher education while under the contract as migrant workers. Various previous research on migrant workers mostly put them as